Agama dengan Keikutsertaan Keluarga Berencana (KB) dan Pemilihan Jenis Alat Kontrasepsi pada Pasangan Usia Subur (PUS) di Desa Argomulyo Sedayu Bantul Yogyakarta - Eva Dyah Pratiwi; Susiana Sariyati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Family Planning (FP) in view of religion is still arise differences of opinion, where there are allow and forbid the recommended types of contraceptives in family planning programs. Based on the interviews with 30 respondents, 10 of them said that religion permits do family planning, 15 of them do not understand what religion does not permit or allow the use of contraceptives, 5 of them said that religion does not allow the use of contraceptives because of their belief in family planning was considered refusing sustenance given (children). The purpose of this study was to determine the relationship between religion in family planning participation and contraceptives selection of reproductive age couples in Argomulyo village, Sedayu, Bantul, Yogyakarta Year 2014. This study was observational with cross sectional design. The Results showed that there was 67.2% of Muslim participated FP, 80% of Christians and 55.6% of Catholics. 71.35% respondents were believing and participated FP and 66.5% respondents does not believe and participate FP. Most of respondents choose injection contraceptives, there was 28.4% in Islam, 20% of Christians, and 44.4% of Catholic. Respondents who believe in FP 31.6% choose injection contraceptive and 27.9% respondents who did not believe in FP also choose injection contraseptive. In conclusion, there was no relationship between religion and family planning participation, there was no correlation between faith and family planning participation, there was no relationship between religion and contraceptive selection, there was a relationship between faith and contraceptive selection.